PROGRAM MEREVITALISASI BAHASA DAERAH MELALUI PEMBELAJARAN MENULIS CERITA PENDEK BAGI SISWA SEKOLAH DASAR - Junaidi, Junaidi; Rasyid, Harunnun; Ali, Muhammad; Wardani, Vera (Universitas Jabal Ghafur, 2025)
This community service activity aims to revitalise the use of the Acehnese language through the teaching of short story writing at SD Negeri Kp. Blang Iboih, Simpang Tiga Sub-district, Pidie Regency. The implementation methods include observation, socialisation, training, mentoring, and a student work exhibition. The results indicate an improvement in students’ literacy skills, along with the emergence of cultural awareness and pride in the regional language. This activity demonstrates that a creative writing approach can serve as an effective strategy for preserving local languages in primary education settings.